The impacts of heat waves on hospital admissions and mortality in the Fethiye province of Turkey - AKKOYUNLU, BÜLENT OKTAY (My University, 2023)
tHeat waves (HWs) are one of the most important atmospheric events that negatively affect human health. In this study, HWs which occurred between May 1 and September 30, 2019 in Fethiye Province (SW Turkey) were investigated for their effects on human health. For this purpose, as a first step, percentile-based threshold criteria and at least three consecutive days\" methodology were applied to the daily maximum temperatures to identify HWs. Using these criteria, a total of 3 HWs (HW 1, HW 2, and HW 3) with lengths of 6, 7, and 5 days, respectively, were found in 2019. In statistical analyses, hospital data recorded on HW days (including the 3 lag days) on reference days were compared using the logarithmic Z test method. Hospital data between May 1 and September 30 in the 5 years between 2014 and 2018 were used as reference data. As a result, in the 3 HWs that occurred in 2019, the risk ratios (RRs) and their confidence intervals in HW 1, HW 2, and HW 3 at hospital admissions were 1.09 (95% CI: 1.06-1.12), 1.11 (95% CI: 1.08-1.14), and 1.13 (95% CI: 1.09-1.16), (p < 0.05), respectively. When the effect of HW on death was examined, the RR values and confidence intervals in HW 1, HW 2, and HW 3 were 1.90 (95% CI: 1.04-3.46), 1.96 (95% CI: 1.03-3.75), and 2.18 (95% CI: 1.13-4.20), (p < 0.005), respectively. As a result, it was found that a total of 22 extra deaths occurred when three HWs were recorded in 2019. When the deaths were analysed by age, it was seen that the most affected group was the elderly (≥65 years), accounting for 82% of deaths. It was determined that 64% of the deaths were male, and 36% were female. These results show that HWs in Fethiye are an important natural disaster that negatively affects human health.
Keywords: Tıp; Dahili Tıp Bilimleri; Aile Hekimliği; Sosyal ve Beşeri Bilimler; Sosyoloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Family Medicine; Social Sciences and Humanities; Sociology; Health Sciences; Klinik Tıp (MED); Sosyal Bilimler (SOC); Klinik Tıp; Sosyal Bilimler Genel; SAĞLIK BAKIM BİLİMLERİ VE HİZMETLERİ; KAMU, ÇEVRE VE İŞ SAĞLIĞI; Clinical Medicine (MED); Social Sciences (SOC); CLINICAL MEDICINE; SOCIAL SCIENCES, GENERAL; HEALTH CARE SCIENCES & SERVICES; PUBLIC, ENVIRONMENTAL & OCCUPATIONAL HEALTH; Sağlık Politikaları; Halk, Çevre ve İş Sağlığı; Health Policy; Public Health, Environmental and Occupational Health; Fethiye; Heat waves; Hospital admissions; Morbidity; Mortality